1988
DOI: 10.1530/jrf.0.0820787
|View full text |Cite
|
Sign up to set email alerts
|

Major genes control hormone-induced ovulation rate in mice

Abstract: Summary. The present study examined the magnitude of genetic variation, mode of inheritance and number of loci controlling major genetic differences in hormone\x=req-\ induced ovulation rate in mice. Mice were injected with 5 i.u. PMSG at 28 days of age and 5 i.u. hCG at 30 days, and hormone-induced ovulation rate was determined from counts of oviducal eggs in cumulus the next morning. Six-fold genetic differences in induced ovulation rate were detected amongst strains, ranging from a low mean ( \ m=+-\ s.e.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
3

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
4
39
3
Order By: Relevance
“…PMSG at 28 days and 5 i.u. hCG at 30 days (Spearow, 1988 (Brown & Forsythe, 1974;Dixon, 1983 Means within columns with different superscripts differ significantly (P < 0-05). (P < 001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…PMSG at 28 days and 5 i.u. hCG at 30 days (Spearow, 1988 (Brown & Forsythe, 1974;Dixon, 1983 Means within columns with different superscripts differ significantly (P < 0-05). (P < 001).…”
Section: Introductionmentioning
confidence: 99%
“…Major genetic differences in hormone-induced ovulation rate in young mice have been identified (Spearow, 1988): a comparison of parentals, Fl and F2 crosses, revealed that a 5-fold difference in hormone-induced ovulation rate between strains A/J and SJL/J was due to the action of about 2-3 loci, and a 6-fold difference in hormone-induced ovulation rate between strains A/J and C57BL/6J was due to the action of about 3^1 loci. These genetic differences in hormone-induced ovulation rate at 28 days of age could have been due to genetic differences in (1) age at puberty, (2) maturation and ovulation of follicles by endogenous gonadotrophins, (3) maturation of follicles by endogenous gonadotrophins and ovulation by exogenous gonadotrophins, (4) age-dependent responses to gonadotrophins, or (5) ovarian responsiveness to exogenous PMSG and hCG.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second factor, production of fertilized eggs, depends on biological factors that are not always under control of the investigator. For example, some inbred strains respond poorly to superovulation treatments (Spearow, 1988) and produce few eggs for fertilization. Other inbred strains, such as PL/J have poor sperm quality that affect numbers of fertilized eggs (Pyle & Handel, 2003;T.…”
Section: Discussionmentioning
confidence: 99%